Fiscal Decentralisation and Economic Theory - Slavinskaite, Neringa (Journal of Business and Legal Sciences / Revista de Ciências Empresariais e Jurídicas, 2015)
There is no complete overview or discussion of the literature of the economics of federalism and Fiscal decentralization, even though scholarly interest in the topic has been increasing significantly over recent years. This paper provides a general, brief but comprehensive overview of the main insights from the literature on fiscal federalism and decentralization. In doing so, literature on fiscal federalism and decentralization is grouped into two main approaches: "first generation of theories" and "second generation of theories".